Correlation of total organic C, particulate and mineral‐associated C fractions with strength indicators in Oxisols - de Lima, Renato P.; Tormena, Cassio A.; Menillo, Rafael B.; La Scala Júnior, Newton [UNESP]; da Silva, Anderson R.; Souza, Zigomar M.; Cerri, Carlos E. P.; Cherubin, Maurício R. (Wiley, 2025)
Abstract The specific role of each fraction of soil C (i.e., particulate [POC] or mineral‐associated organic carbon [MAOC]) in each soil strength mechanism remains unexplored. We investigated the relationships of total organic C and its physical fractions with soil strength of two tropical soils (sandy clay loam [SCL soil ] and sandy clay [SC soil ]). We measured soil strength indicators from oven‐dry aggregates [tensile strength ( σ t )] and some related to soil compaction [precompression stress ( σ p ), compression index ( λ ), and penetration resistance (SPR) at constant matric potential (−100 hPa)]. These soil strength indicators were used as response variables in path analyses to determine direct effects of C, MAOC, and POC mediated by key physical strength inducers (bulk density or water content). Results suggest a C role conferring soil strength verified by positive correlation with tensile strength and SPR increase, positively influenced by MAOC in SCL soil and C/POC/MAOC in SC soil . For SPR, the C effect was mediated by water content or bulk density (i.e., indirect contribution for correlation). Organic C, in turn, showed limited effect on soil compressibility. These findings indicate that increases in soil carbon that enhance aggregate mechanical strength and penetration resistance do not result in reduced soil compressibility (i.e., resistance to compaction). In sandy clay loam soils, MAOC plays a key role in increasing soil strength, whereas all carbon fractions contribute to strength gains with increasing clay content. Thus, while organic carbon can promote beneficial structural stability in the long term, it may also increase SPR, which affects root growth. Core Ideas Organic carbon correlates positively with soil strength. Clay enhances the role of C in soil aggregate strength. Soil compressibility strength is minimally affected by C. Continuous C input increases soil penetration resistance in long‐term systems. Plain Language Summary Healthy soil is important for growing crops, and part of what keeps soil strong is the amount of organic carbon it has. But not all carbon in the soil works the same way. In this study, we looked at two types of tropical soils to understand how different kinds of carbon help the soil stay firm and resist being pressed down. We found that carbon attached to tiny minerals helps the soil stay strong, especially in sandy soils. In a clay soil, all types of carbon helped. But even when carbon made the soil stronger, it did not always stop it from getting compacted. This means that adding more carbon can be good for soil structure, but it might also make it harder for plant roots to grow. These results help us better manage soil to grow food in a healthy and sustainable way.